Cultural Adaptations in Maintaining Religious Harmony in the Labor Community at PT Satya Krisma Usaha Factory in Tebo Ilir Jambi - Rara Anggraini (Islam Transformatif : Journal of Islamic Studies, 2021)
This study describes the cultural adaptation carried out by the factory worker community consisting of various ethnicities and religions at PT Satya Krisma in Tebo Ilir Jambi, in maintaining religious harmony. This research uses qualitative research that emphasizes the depth of information obtained through interviews and is also supported by field observation methods. The results of the study show that first, the reality of life that occurs in the community of factory workers in the village of Betung Bedarah Barat is very harmonious and harmonious until now, because the community always respects and respects, and always prioritizes mutual assistance and cooperation. Second, factors that influence the occurrence of harmony are internal and external factors, internal factors are tolerance, dialogue between communities and there is also awareness of diversity. The external factor is that there are institutions that support religious harmony, namely the involvement of the government, traditional leaders and religious leaders. Third, in maintaining harmony, they have strategies including strengthening brotherhood, the role of traditional leaders, religious leaders, and maximizing regulations and the role of local governments.Penelitian ini menjelaskan tentang adaptasi budaya komunitas buruh pabrik dalam menjaga kerukunan umat beragama di PT Satya Krisma di Tebo Ilir Jambi. Penelitian ini menggunakan jenis penelitian kualitatif yang menekankan pada aspek kedalaman informasi yang diperoleh melalui wawancara dan didukung pula oleh metode observasi lapangan. Hasil penelitian menunjukkan bahwa  pertama, realita kehidupan yang terjadi pada komunitas buruh pabrik di desa Betung Bedarah Barat sangat rukun dan harmonis sampai saat ini, karena masyarakat selalu menghargai dan menghormati, dan selalu mengedepankan sikap saling bantu dan bekerja sama. Kedua, faktor yang mempengaruhi terjadinya keharmonisan yaitu faktor internal dan eksternal, faktor internal yaitu adanya sikap toleransi, dialog antar masyarakat dan juga terdapat kesadaran. Faktor eksternal yaitu terdapat lembaga yang menjadi pendukung dalam kerukunan umat beragama yaitu adanya keterlibatan pemerintah, tokoh adat dan tokoh agama. Ketiga, dalam mempertahankan kerukunan, mereka mempunyai strategi di antaranya memperkuat tali persaudaraan, melibatkan tokoh adat, tokoh agama, dan memaksimalkan peran regulasi pemerintah daerah.